(untitled) (Neo Science Peer Reviewed Journal, 2023)
The development of effective communication skills is of utmost importance for future engineers in order to succeed in their professional careers. This article explores the principles underlying the development of communicative competence and highlights the pedagogical conditions necessary for cultivating effective communication skills among engineering students. Drawing upon relevant literature and research, this article provides insights into the theoretical foundations of communicative competence and practical strategies for its development. By implementing the suggested pedagogical conditions, educators can facilitate the holistic development of future engineers’ communicative competence, thereby equipping them with the necessary skills for professional success.